Experiences of First-Time Mothers With Persistent Pelvic Girdle Pain After Childbirth: Descriptive Qualitative Study. Issue 10 (1st October 2015) - Wuytack, Francesca; Curtis, Elizabeth; Begley, Cecily
Abstract : Background: Pelvic girdle pain (PGP) is common during pregnancy and negatively affects women's lives. When PGP persists after the birth, the way it affects women's lives may change, particularly for first-time mothers as they adjust to motherhood, yet the experiences of women with persistent PGP remain largely unexplored. Objectives: The objective of this study was to explore primiparous women's experiences of persistent PGP and its impact on their lives postpartum, including caring for their infant and their parental role. Design: This was a descriptive qualitative study. Methods: Following institution ethical approval, 23 consenting primiparous women with PGP that had started during pregnancy and persisted for at least 3 months postpartum participated in individual interviews. These interviews were recorded, transcribed, and analyzed using thematic analysis. Results: Four themes emerged: (1) "Putting up with the pain: coping with everyday life, " in which women put up with the pain but had to balance activities and were grateful for support from family and friends to face everyday challenges; (2) "I don't feel back to normal, " in which women's feelings of physical limitations, frustration, and a negative impact on their mood were described; (3) "Unexpected, " in which persistent symptoms were unexpected for women due to a lack of information given about PGP; and (4) "What next?, " in which the future of women's symptoms was met with great uncertainty, and they expressed worry about having another baby. Conclusion: For first-time mothers, having persistent PGP postpartum affects their daily lives in many ways. These findings provide important information for health care providers, which will improve their understanding of these women's experiences, will enhance rapport, and can be used to provide information and address concerns to optimize maternity care during pregnancy and beyond.